2019
DOI: 10.1111/jvim.15437
|View full text |Cite|
|
Sign up to set email alerts
|

Morphometric analysis of spinal cord termination in Cavalier King Charles Spaniels

Abstract: Background There is an association between Chiari malformations, syringomyelia (CMSM) and tethered cord syndrome (TCS) in people, suggesting Cavalier King Charles Spaniels (CKCS) with CMSM could also have TCS. Currently there are no data on the position of the caudal spinal cord structures in CKCS. Objective To describe and compare location of spinal cord termination in CKCS with weight‐matched controls and to examine the relationship between SM and spinal cord termination. Animals Thirty‐nine CKCS and 33 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 45 publications
5
22
1
Order By: Relevance
“…In previous work, we found that TL but not cervical SM was significantly associated with the location of dural sac termination in CKCS. 6 In the current study, we were unable to draw statistical comparisons for dogs with cervical SM because only 2/48 dogs (4%) had cervical SM only. Dural sac termination appeared to be located more caudally in dogs with lumbar SM, but this relationship was not significant ( Figure 3).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In previous work, we found that TL but not cervical SM was significantly associated with the location of dural sac termination in CKCS. 6 In the current study, we were unable to draw statistical comparisons for dogs with cervical SM because only 2/48 dogs (4%) had cervical SM only. Dural sac termination appeared to be located more caudally in dogs with lumbar SM, but this relationship was not significant ( Figure 3).…”
Section: Discussionmentioning
confidence: 75%
“…Cavalier King Charles spaniels (CKCS) are affected by Chiari‐like malformation (CM) and syringomyelia (SM) causing neuropathic pain and parasthesias of the head and neck region. Syringomyelia was first noted in the cervical spinal cord using magnetic resonance imaging (MRI) but more extensive imaging protocols identified its presence in the thoracic and lumbar spinal cord 1‐6 . The etiology of clinical signs in CKCS with Chiari‐like malformation with syringomelia (CMSM) is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to dogs with Chiari-like malformation only, dogs with syringomyelia have more extreme brachycephaly with craniocervical junction deformation, including cervical flexure, change in angulation of the odontoid peg, increased proximity of the atlas to the skull (often referred to as atlanto-occipital overlapping), kinking or elevation of the craniospinal junction, and loss of the cisterna magna [ 13 , 75 , 82 , 83 , 84 ]. Changes in conformation of the spinal canal and cord may also contribute [ 85 , 86 ]. The authors propose that syringomyelia develops due to a combination of reduced CSF absorption though nasal lymphatics, reduced venous drainage, altered neuroparenchymal compliance, and reduced CSF movement through the lateral apertures or craniocervical junction.…”
Section: Csf Disorders In Brachycephalic Animalsmentioning
confidence: 99%
“…De Decker et al (2015) suggests that it can be hard to diagnose this due to natural variations of the conus medullaris in dogs. In cavalier King Charles spaniels, Sparks, Robertson, and Olby (2019) examined the possibility of the association of tethered cord syndrome with Chiari malformation and syringomelia both of which are common in the breed. In the cavalier King Charles spaniel, they noted that the dural sac is more caudally located than other breeds of comparable weight, and the spinal cord is also caudally displaced.…”
Section: Spinal Ntdsmentioning
confidence: 99%